Measurement of economic returns and environmental and social for green sector trade A prospective study in institutions of Basra to focus on the electricity sector - الشاوي هاني فاضل; عيسى خليل ابراهيم; عبد الحسين عامر جميل (Journal of Economics and Administrative Sciences, 2013)
Environmental risk growing Become challenge "and a matter of controversy and concern to many of those concerned with environment, social, economic, and the same happens with the administrative rather than in isolation for this movement, as the issues of climate change Disturbed and troubled him, especially after what caused the risk of destruction, and irresponsibility , chaos, and the futility of resources, crops, fields, nature and homes and reactors, and after what happened in Japan from the scourge of "Hurricane tsunami " and earthquakes successive accompanied him and what became of him by surprise catastrophic affected the economy and the universe and man as the first first victim, on the basis of these cases took the researchers the idea of ​​research marked by (measuring economic returns and environmental and social for green sector trade) titles "of the study. The study hypothesis that "contributes to the proper utilization of alternative energy sources or green to improve economic returns and environmental and social development in industrial enterprises" Find taken to promote the concepts of sustainability (economic, environmental and social) goals, "head of him as well as contribute to the dissemination of concepts related to the provision of a balanced share of existing energy sources for the present generation and future generations a vision and social responsibility and ethical future. The study relied on a descriptive analytical method as a way to it. And three were chosen enterprises in Basra (oil, gas, electricity) room on the ground "for the application. Since been adopted scale developer after presenting a number of specialized subject matter under examination and the introduction of Ptogerathm reflect the identification and distributed to random sample of (75) members "represent a society composed of three institutions were selected from groups of randomly select the number of each group of (25) individuals have the capabilities and reliability to enable them to professionally answer the vocabulary. On this basis, the study found several conclusions, including:- Lack of attention to cultural and political activities in the field of alternative energy. - The limited relationship and the impact of (political activities, and cultural activities) in the promotion of alternative energy products.